Production of colony-stimulating factors (CSFs) during infection: separate determinations of macrophage-, granulocyte-, granulocyte-macrophage-, and multi-CSFs. - Cheers, C (1988)
After infection of mice with Listeria monocytogenes, elevated levels of colony-stimulating factors (CSFs) in the serum were quantitated by six different assays: ability to stimulate colony formation, the proliferation of 2 suspension of bone marrow cells (both measuring total colony-stimulating activity), a radioimmunoassay for macrophage-CSF (CSF-1), the WEHI-3B differentiation assay for granulocyte-CSF, and proliferation of 32D-c1-3 and FDC-P1 cell lines (specific for multi-CSF and either multi- or granulocyte-macrophage-CSFs, respectively). The great bulk of serum colony-stimulating activity represented macrophage- and granulocyte-CSFs, with small but measurable amounts of granulocyte-macrophage-CSF. The degree of elevation of serum CSF depended on the infecting dose used and the numbers of bacteria growing in the spleens and livers of the two mouse strains compared, i.e., L. monocytogenes-resistant C57BL/10 and susceptible BALB/cJ. The increase in serum CSFs occurred before the peak in bone marrow granulocyte-macrophage progenitors and before the reduction in bacterial numbers which follows the onset of specific cell-mediated immunity.